The genome sequence of the Common Carder Bee, Bombus pascuorum (Scopoli, 1763) [version 1; peer review: 2 approved] - Duncan Sivell; Olga Sivell; Liam M. Crowley (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Bombus pascuorum (the Common Carder Bee; Arthropoda; Insecta; Hymenoptera; Apidae). The genome sequence is 307.5 megabases in span. Most of the assembly is scaffolded into 17 chromosomal pseudomolecules. The mitochondrial genome has also been assembled and is 21.9 kilobases in length. Gene annotation of this assembly on Ensembl identified 12,999 protein coding genes.